Safety performance analysis of signalized intersections in Abu Dhabi using a mixed research approach - Alghfeli, Abdulla Hamad Obaid Hamad (2023)
Even though Abu Dhabi government has taken a number of steps to reduce the number of road accidents, and fatalities as well as injuries associated with them, the city has continued to experience high number of traffic accidents especially at the intersections. According to Abu Dhabi’s Police Traffic Engineering Department, in 2013 for instance, of all the 1400 severe traffic accidents, signalized intersections were responsible for 240 traffic accidents which was the highest contribution by a single factor. On the other hand, red light violation (RLV) is considered one of the major contributors of traffic accidents in many cities including Abu Dhabi. Several studies done elsewhere have attributed this to reaction times after activation of red light but not in Abu Dhabi which may help the authorities implement appropriate signal phasing timings at the intersections. Moreover, in an effort to homogenize Abu Dhabi City’s Road traffic rules with those of international rules, Abu Dhabi government removed the 20 kph speed buffers on all roads in 2018. This was implemented in such a way that the enforcement speed and the posted speed have the same value. However, few studies have examined the effect of implementing policies to the safety performance at the signalized intersections. The study aims at improving the safety performance of these intersections by determining operational and geometric factors affecting safety performance of the Abu Dhabi’s Signalized intersection; determining the effect of drivers’ reaction time; determining the effect of removal of speed buffers on the safety performance of Abu Dhabi’s Signalized intersections; ascertain the recommendations used by road safety audit staff while evaluating signalized intersections; and proposing practical and feasible safety performance indicators that could act as a standard to the administrative authorities for developing the signalized intersections. The objectives were achieved via quantitative research methodology (objectives 1 to 3) and qualitative research (Objective 4 and 5). The data were analysed via descriptive and inferential statistics (negative binomial regression) and thematic analysis. The result shows that when compared to other intersections, 3-leg intersections tend to be more sensitive to variations of the geometric and operational factors. This is such that the size of the mid-island (major direction), the size of separation between through and left and number of lanes in minor left are negatively related with number of accidents. The size of mid-island (minor direction), number lanes in the main through, number of pedestrian crossings, intersection speed, and average hourly traffic are positively related at this intersection. In terms of objective 2, the research found that most of the red violations and hence traffic accidents occur between less than 1s to 2 to 3 seconds after activation of red light at the intersections which indicates drivers’ reaction is a major contributor safety performance of these intersections. In terms of objective 3, the study found that introduction of speed buffers indeed reduced traffic accidents, and thus improved the safety performance of the intersections. In terms of objectives 4 and 5, the research found that: there is the poor implementation of guidelines by the auditors. Based on the above results, it is recommended that other emirates in UAE should consider implementing the policy; safety manual should be improved to conform to the internationally renowned manuals.